PENGARUH PENDAPATAN ASLI DAERAH, BELANJA PEMERINTAH DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI (PDRB) KAB DAN KOTA DI JAWA TENGAH - Riyan Wahyu Budiaji, 09.05.52.0157; Kartika, Andi (Students Journal of Accounting and Banking, 2014)
This study examined the effect of revenue on the Sar (PAD), Government Expenditure and Employment to GDP district and city in Central Java. The population in this study is a county and cities in Central Java. The sample in this study was done by using census. Census sampling technique is, the entire population in this study serve as the research sample. Â Thus, the samples in this study were 35 districts / cities in Central Java.Based results indicate that the original income has a significant effect on GDP, Government Spending Levels have no significant influence on the direction of GDP, royal power has no significant influence on the direction of GDP. Local revenues, Government spending and labor together have an influence on GDP.Keywords: PAD, Government Spending, Employment, GDPÂ